Conceptual Analysis of the Merdeka Curriculum and Its Implementation at MAN 1 Sukabumi - Zahra, Nabila Himmatina; Suparto (Belajea: Jurnal Pendidikan Islam, 2025)
This research describes the understanding of the head of MAN 1 Sukabumi and the educators regarding the Merdeka curriculum. This understanding led the head of the madrasah to implement the Merdeka curriculum in the madrasah. The implementation consists of the preparation stage, implementation stage, and strengthening the Pancasila student profile and raḥmatan lil’ālamīn profile. This research employs a qualitative case study method. Data collection methods were in-depth interviews, observation, and documentation studies. This research found that (1) The Merdeka curriculum is understood by educators at MAN 1 Sukabumi as an educational tool that facilitates diverse intracurricular learning, focuses on essential material, and develops student competencies, gives the school the authority to create a curriculum under its characteristics, and supports strengthening Pancasila student profile and raḥmatan lil’ālamīn profile. (2) The Merdeka curriculum at MAN 1 Sukabumi has been implemented optimally, except for several aspects that have not been fully implemented. There are eleven aspects of implementation at the ready stage, three aspects at the developing stage, and one aspect at the initial stage. (3) Strengthening the student profile of Pancasila and raḥmatan ālamīn at MAN 1 Sukabumi is carried out through projects with the themes of local wisdom, Pancasila democracy, and Bhinneka Tunggal Ika.